Numerical analysis and performance investigation of new hybrid system integrating concentrated solar flat plate collector with a thermoelectric generator system. (March 2020) - Faddouli, A.; Labrim, H.; Fadili, S.; Habchi, A.; Hartiti, B.; Benaissa, M.; Hajji, M.; EZ-Zahraouy, H.; Ntsoenzok, E.; Benyoussef, A.
Abstract: Advanced solar thermal devices with a high performance/cost ratio is a major concern nowadays. In this paper, we investigate the energetic efficiency of a new concept based on a direct coupling of a solar water heater with a thermoelectric module, in order to exploit the maximum of the solar spectrum, produce heat and electricity at the same time and improve the normal solar collector efficiency. An unsteady-state mathematical model of the system is presented in details to describe the system behavior. Using state-of-the-art thermal transfer calculations, the differential equations of the global system were established and solved numerically. The system model is solved using MATLAB program, while the finite difference method is based. Our major finding shows that the new hybrid system significantly improves the storage process by controlling the flow rate according to the concentration ratio variation. This flow rate attains a capacity of 1200.453 L/day, for 0.92 × 1.9 × 0.05 m 3 a collector tilted at 30° under 20 suns, and produces a significant additional electrical energy about 10.41 Watts, which is very promising for future thermal/electrical applications. Highlights: A novel solar thermal thermoelectric system is proposed and explored. Theoretical model is presented, numerically simulated, and smart program is developed. The effect of the cooling system on the thermoelectric performance is analyzed. Evaluated performances of this system under real concentrated sunlight are presented. The system produces heat, electricity and increase the quantity of hot water stored.